(untitled) (Texas Journal of Philology, Culture and History, 2023)
The article analyzes the specific characteristics of verbs in English and Uzbek languages from a scientific and practical point of view. During the analysis, the specific features of the verbs of the two languages, the place of auxiliary verbs and independent verbs in the sentence, suffixes and affixes added to verbs as well as definite and indefinite forms of the verb were studied